Kualitas Pelayanan Sertifikasi Tanah (Studi Tentang Layanan Sertifikasi PRONA di Kelurahan Bandungrejosari Kota Malang) - Helmi Wisnu Satria (Jurnal Administrasi Publik, 2015)
Abstract: Service quality of land certification (Study About Service Of Certification Through Prona In Bandungrejosari Village, Malang City). Ministry of Agrarian and Spatial/BPN RI has the land certification program aimed for middle-class economy cheaply, easy and mass through the National Agricultural Operations Project (PRONA). PRONA certification is the mandate from decree the minister of home affairs No. 189 on 1981 about PRONA which then implemented by BPN Office City / Regency in Indonesia. During one of work program, PRONA implemented by BPN Office Malang with based a commitment on the quality of public service delivery. The purpose of this study are to analyze the quality of the land through PRONA certification services in the Bandungrejosari  Village, Malang City, also supporting and inhibiting factors in the process of certification services PRONA. This study used a qualitative descriptive study. The quality of certification services PRONA in the Bandungrejosari  Village, Malang, can be said have a good quality. The discovery of the principle quality public services such as the simplicity of the stage, clarity and certainty, security certification process of PRONA, disclosure of all information about certification PRONA, efficiency, economic, equal justice to all the people who are entitled to receive certification PRONA and punctuality. And then, there are supporting factors PRONA certification which includes the completion time of the one year budget, infrastructure, public enthusiasm. Then the inhibiting factors which include lack of personnel in the field of measurement and data collection juridical length. Keywords : Quality of Service, Certification PRONA Abstrak: Kualitas pelayanan sertifikasi tanah (Studi tentang layanan sertifikasi PRONA di Kelurahan Bandungrejosari Kota Malang). Kementerian Agraria dan Tata Ruang/BPN RI memiliki program pensertifikatan tanah yang ditujukan kepada kalangan ekonomi menengah kebawah secara murah, mudah dan massal melalui Proyek Operasi Nasional Agraria (PRONA). Landasan PRONA yaitu mengacu pada Surat Keputusan Menteri Dalam Negeri Nomor 189 Tahun 1981 tentang PRONA. PRONA diimplementasikan oleh BPN Kantor Kota Malang dengan didasari komitmen penyelenggaraan pelayanan publik yang berkualitas. Tujuan penelitian ini untuk menganalisa kualitas pelayanan sertifikasi tanah melalui PRONA di Kelurahan Bandungrejosari Kota Malang, serta faktor pendukung dan penghambat dalam proses pelayanan sertifikasi PRONA tersebut. Penelitian ini menggunakan penelitian deskriptif kualitatif. Kualitas pelayanan sertifikasi PRONA di Kelurahan Bandungrejosari Kota Malang dapat dikatakan berkualitas. Diketemukannya asas pelayanan publik yang berkualitas seperti kesederhanaan tahapan, kejelasan dan kepastian, keamanan proses sertifikasi PRONA, keterbukaan segala informasi tentang sertifikasi PRONA, efisiensi, ekonomis, keadilan yang merata kepada setiap masyarakat yang berhak menerima sertifikasi PRONA dan ketepatan waktu. Selanjutnya terdapat faktor pendukung sertifikasi PRONA yang meliputi  waktu penyelesaian dalam satu tahun anggaran, sarana dan prasarana, antusiasme masyarakat. Kemudian faktor penghambat yang meliputi kurangnya aparatur dibidang pengukuran dan lamanya pengumpulan data yuridis.   Kata kunci: Kualitas Pelayanan, Sertifikasi PRONA